The role of irreversible pan-HER tyrosine kinase inhibitors in the treatment of HER2-Positive metastatic breast cancer - Wu, Zihong; Wang, Jiamei; You, Fengming; Li, Xueke; Xiao, Chong (Frontiers in Pharmacology, 2023)
Human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) is the leading cause of cancer death in women. For patients with HER2-positive MBC, after the failure of multiple lines of treatment, there is no optimal line of therapy. A series of clinical trials confirmed that treatment with irreversible pan-HER tyrosine kinase inhibitors (TKIs) in combination with chemotherapy significantly improves patients’ survival outcomes. In this review, we focus on the pathogenesis of HER2-positive breast cancer, current standard treatments, mechanisms of approved irreversible TKIs, and key clinical trials. The available findings suggest that irreversible pan-HER TKIs, such as pyrotinib and neratinib, in combination with chemotherapy, represent a beneficial salvage therapy for patients with HER2-positive MBC with manageable toxicity. However, further studies are needed to assess the efficacy and safety of this combination therapy.